PEMANFAATAN MEDIA APLIKASI QUICK MATH UNTUK MEMUDAHKAN SISWA PADA PEMBELAJARAN MATEMATIKA - Faizatul Widat; Hamidatul Maulidah; Aisyatur Rosyidah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
In the context of mathematics education, many students face difficulties in understanding basic and advanced concepts which is often caused by less interactive teaching approaches and a lack of direct feedback. To overcome this problem, this research explores the use of the Quick Math application as an alternative learning media that can improve students' understanding of mathematics. This application offers a technology-based approach designed to make mathematics learning more engaging and effective. The aim of this research is to assess the effectiveness of the Quick Math application in facilitating the mathematics learning process for students and to evaluate the extent to which this application can help students overcome their difficulties in mathematics. The research methodology involves using the Quick Math application in a classroom environment over a certain period, involving a group of students who carry out exercises and evaluations through this application. Data was collected through observation, interviews and analysis of student learning outcomes before and after using the application. The research results show that using the Quick Math application significantly increases students' understanding of mathematics material. Students showed improvements in their ability to solve problems and understand mathematical concepts, thanks to the immediate feedback and interactive features provided by the app. In addition, student motivation and engagement in the learning process also increases, thanks to the gamification elements integrated in the application. This research highlights that application media such as Quick Math can be an effective tool in supporting mathematics learning and offering practical solutions to improve student learning outcomes.